2020
DOI: 10.1113/jp279607
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII activity contributes to homeometric autoregulation of the heart: A novel mechanism for the Anrep effect

Abstract: The Anrep effect represents the alteration of left ventricular (LV) contractility to acutely enhanced afterload in a few seconds, thereby preserving stroke volume (SV) at constant preload. As a result of the missing preload stretch in our model, the Anrep effect differs from the slow force response and has a different mechanism. r The Anrep effect demonstrated two different phases. First, the sudden increased afterload was momentary equilibrated by the enhanced LV contractility as a result of higher power stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 52 publications
(79 reference statements)
0
37
0
Order By: Relevance
“…Although the inhibition of CaMKII seems like a promising treatment strategy in CPVT, this strategy might have unappreciated effects on health and disease (Beckendorf et al, 2018 ). This includes hampered cardiac contractile response to exercise training (Burgos et al, 2017 ) and increased afterload (Reil et al, 2020 ), as well as adverse effects in other organs (Beckendorf et al, 2018 ). Thus, increased understanding of how the regulation of CaMKII contributes to the arrhythmogenic phenotype in CPVT might help develop new treatment strategies to prevent arrhythmias, while preserving the physiological effects of CaMKII.…”
Section: Introductionmentioning
confidence: 99%
“…Although the inhibition of CaMKII seems like a promising treatment strategy in CPVT, this strategy might have unappreciated effects on health and disease (Beckendorf et al, 2018 ). This includes hampered cardiac contractile response to exercise training (Burgos et al, 2017 ) and increased afterload (Reil et al, 2020 ), as well as adverse effects in other organs (Beckendorf et al, 2018 ). Thus, increased understanding of how the regulation of CaMKII contributes to the arrhythmogenic phenotype in CPVT might help develop new treatment strategies to prevent arrhythmias, while preserving the physiological effects of CaMKII.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical and experimental data also suggest that cMyBP-C phosphorylation modulates the relative cross-bridge detachment rate with respect to attachment rate and thereby mediates diastolic function [ 55 ]. Previously, we provided evidence on the direct impact of oxidate stress on CaMKII-mediated myofilament protein phosphorylation and function [ 56 ], of which this interaction is likely important in the post-ischemic heart as well. Finally, upstream signaling mechanisms might also show heterogeneity, since interventricular differences were reported in inotropic responses to α 1 -adrenergic stimulation in control mice [ 57 ], as well as in adenylyl cyclase activities in LV MI-induced HF rats [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of those, the γ and δ isoforms are predominantly expressed in the heart. In addition, CaMKII activity is primarily regulated by four posttranslational modifications, including the Ca 2+ /calmodulin-binding, autophosphorylation [43,44], oxidation [45], O-linked N-acetylglucosamination (O-GlcNAc) [46], and S-nitrosylation [47] of CaMKII. Several studies have confirmed that the sustained activation of CaMKII modulates potassium channels [48], whereas the inhibition of CaMKII may prevent the internalization of K ATP channels caused by ischemia, thereby reducing the vulnerability of CMs to injury [49,50].…”
Section: Discussionmentioning
confidence: 99%